Augmented boiling heat transfer on a copper nanoporous surface and the stability of nano-porosity in a hydrothermal environment. (November 2015) - Tang, Biao; Zhou, Rui; Lu, Longsheng; Zhou, Guofu
Highlights: A novel CNPS is fabricated by an in-situ SA&D approach. Bubble dynamics and nucleate boiling heat transfer on the CNPS were studied. The stability of NPC under boiling environment was systematically studied. A continuous coarsening process of NPC controlled by surface diffusion was confirmed. An equation was given to predict the feature-size dependent stability of the NPC. Abstract: A novel in-situ surface alloying and dealloying (SA&D) approach is proposed for the fabrication of copper nanoporous surface (CNPS). The bubble dynamics and nucleate boiling heat transfer performance of the CNPS were investigated by high-speed visualization. The bi-continuous porous structures on CNPS facilitate the onset of boiling and significantly enhance the nucleate boiling heat transfer. Bubbles with smaller departure diameter and higher departure frequency on the CNPS were observed compared to those on plain surface, which can be attributed to the differences in wettability and morphology. The chemical and morphological stability of as-dealloyed nanoporous copper (NPC) under saturated boiling environment were systematically studied. The EDS results for different boiling times indicate NPC of excellent chemical stability. The porosity evolution with time of the NPC was recorded by SEM images, and a continuous coarsening process controlled by surface diffusion was confirmed by quantitative analysis of the porosity feature size. A simple equation was given to describe the feature-size dependent stability performance of NPC under the hydrothermal environment.